PENGOLAHAN ARSIP STATIS DI KANTOR ARSIP DAN PERPUSTAKAAN DAERAH KOTA YOGYAKARTA - , FITRIA NURVITA SARI; , Faizatush Sholikhah, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The preparation of the final assignment entitled âThe Arrangement of Archives at Kantor Arsip dan Perpustakaan Daerah Kota Yogyakartaâ represented the results of data collection from the apprenticeship in the Kantor Arsip dan Perpustakaan Daerah Kota Yogyakarta. The apprenticeship aimed at finding out the condition of the static archives in the office and investigating special procedure of archives arrangement. The scope of the problems related to planning coordination before processing, a means to retrieve existing archives and existing legal products. The methods used in the study were interview, participative observation and literature study. The interview aimed at complementing the existing information and obtaining more comprehensive information from resource persons who were experts in archive affairs. The apprenticeship enabled direct observation and participation in the activities of archives arrangement in the Kantor Arsip dan Perpustakaan Daerah Kota Yogyakarta. The method enabled author to directly observe the archives condition, to obtain valid and concrete data related to whole object and the extend to which the knowledge of archive affairs in was implemented in real world situation. Additionally, the author could easily obtain information because she directly played her role in the arrangement of archives in Kantor Arsip dan Perpustakaan Daerah Kota Yogyakarta. Once the data have been collected, the author drew conclusion that the arrangement of the archives in Kantor Arsip dan Perpustakaan Daerah Kota Yogyakarta has not been consistent with the knowledge of good and right arrangement of archives affairs because the existing human resources did not give a good attention to textual archives that the arrangement has not given maximal results as observed in the absence of retrieval means of the archives inventory